PERAN EMOSI MEMEDIASI KEADILAN DISTRIBUTIF, PROSEDURAL DAN INTERAKSIONAL TERHADAP KEPUASAN PEMULIHAN LAYANAN - -, badawi (JURNAL MANAJEMEN DAN AKUNTANSI, 2012)
Abstract: The research objectives were to analyze: the influence of distributive justice, procedural, and interactional, justice in handling customer complaints against emotions, the influence of negative emotions toward the satisfaction of handling customer complaints,  the influence of distributive justice, procedural, and interactional justice on the handling of complaints to the satisfaction of handling complaints, the customers’ negative emotions which reinforce the influence of distributive, procedural, and interactional justice toward satisfaction with service recovery. The respondents of this study were Rumah Makan customers who have a minimum of 5 experience service failure of 110 in amount. The data analysis technique used was Structural Equation Modeling (SEM). The results showed that distributive, procedural, and interactional justice had negative effect on emotions,  emotions can improve satisfaction with service recovery, distributive and procedural justice not significant effects on the satisfaction with service recovery.  Interactional justice had positive and significant effects on the satisfaction with service recovery, emotions may mediate the effect of justice to the satisfaction with service recovery. Key words: distributive, procedural and interactional justice, emotions and         satisfaction with service recovery.